ادارة الجودة الشاملة والاداء: حالات مختارة من الأردن - أخوارشيده, عبد الحكيم عقله (Latakia University Journal - Economic and Legal Sciences Series, 2019)
The current study investigated the relationship between Total Quality Management (TQM) and organizational performance by comparing different cases in private and public sectors in Jordan. The cases represented several sectors such as banking, health care management, and manufacturing. The findings suggested that TQM is a critical approach of management to achieve high performance, efficiency, and effectiveness of organizations. It showed that the field that the organization belongs to influences the types of indicators (measures) used for both TQM and performance. Though the number of cases was small, the study can be practically significant to illustrate the strong relationship between TQM and performance. Moreover, the investigated cases indicated that the TQM is critical approach to achieve the efficiency, effectiveness and performance within organizations, and showed that the specialization of the organizations influence the type of indicators used for both TQM and performance. تهدف هذه الورقة البحثية الى بحث العلاقة بين مؤشرات ادارة الجودة الشاملة ومقاييس الاداء وذلك بمقارنة حالات مختلفة في القطاعين العام والخاص في الأردن. شملت الحالات التي أختيرت في هذه الورقة قطاعات متعددة مثل القطاع البنكي, وادارة الخدمات الصحية, والقطاع الانتاجي. وعلى الرغم من العدد القليل من تلك الحالات, فأن هذه الدراسة يمكن ان تكون دليلا" هام التبرير العلاقة القوية بين تطبيق الجودة الشاملة والأداء.